How a concerned family member, friend or member of the public can help someone with gambling problems: a Delphi consensus study. Issue 1 (December 2016) - Bond, Kathy; Jorm, Anthony; Miller, Helen; Rodda, Simone; Reavley, Nicola; Kelly, Claire; Kitchener, Betty
Abstract Background Gambling is an enjoyable recreational pursuit for many people. However, for some it can lead to significant harms. The Delphi expert consensus method was used to develop guidelines for how a concerned family member, friend or member of the public can recognise the signs of gambling problems and support a person to change their gambling. Methods A systematic review of websites, books and journal articles was conducted to develop a questionnaire containing items about the knowledge, skills and actions needed for supporting a person with gambling problems. These items were rated over three rounds by two international expert panels comprising people with a lived experience of gambling problems and professionals who treat people with gambling problems or research gambling problems. Results A total of 66 experts (34 with lived experience and 32 professionals) rated 412 helping statements according to whether they thought the statements should be included in these guidelines. There were 234 helping statements that were endorsed by at least 80 % of members of both of the expert panels. These endorsed statements were used to develop the guidelines. Conclusion Two groups of experts were able to reach substantial consensus on how someone can recognise the signs of gambling problems and support a person to change.